Illness monitoring in team sports using a web-based training diary - Cunniffe, B.; Griffiths, H.; Proctor, W.; Jones, K. P.; Baker, J. S.; Davies, B. (Clinical Journal of Sport Medicine, 2009)
The article presents a study that aims to design and implement an efficient system to monitor incidences of illness in sports athletes in a team. Study shows 79% as the diary response rate in the reporting of weekly illnesses over the study period. It concludes that players are likely to underreport incidences of banal infections.